The contextualisation of leadership in Paul : applied to English-speaking Methodist Churches in Peninsular Malaysia - Senior, Roger, 1951- (Regnum studies in mission., 2017)
Leadership and its exercise in different cultures is a major issue in today's church. To what extent is it legitimate to use the leadership patterns of the local context and can these be challengedThis book examines Paul's ministry and writings to see how the early church contextualised leadership and to identify some of the theological principles which influenced the process. The outworking of these in the leadership of the English-speaking Methodist churches in Peninsular Malaysia is examined.